An interdisciplinary glance at the latent sides of performance in games - Lebed, F. (World Congress of Performance Analysis of Sport VIII, 2008)
The developed glance at the system`s pre-performance functioning makes it possible to accept the thesis about the pro-active character of human behavior, at least as far as the mutually-active conflicts of sport competition are concerned. This view is cause enough to rethink the role of situational afferentations (in other words, the role of a counteracting opponent) during a process of decision making and then performance in a game. This role is much less than is accepted in the present tradition of scholarly notation of performance analysis (Lebed, 2007). According to this new approach, motivational desire and the prolonged influence of the social environment have such a strong effect on individual consciousness and personality that human behavior becomes more dependent on one`s individual goals, plans and social factors than on the current situational environment. In terms of application, the theoretical analysis presented in this article underlines two essential directions in sport pedagogics. The first possible pedagogical application of this study is in giving proper attention to the latent inputs of a playing system as part of the qualitative background of the performance being analyzed. The second is the obvious necessity to add general and special socialization ("sociological preparation") to the wide accepted "battery" of constructs pertaining to the main contents of sport training (physical or fitness preparation; technical, tactical, and mental preparations).